Synthesis and antibacterial activity of new lactone 1,4-dihydroquinoline derivatives - Laurentiz, Rosangela S. [UNESP]; Gomes, Willian P. [UNESP]; Pissurno, Ana P. R. [UNESP]; Santos, Fernanda A. [UNESP]; Santos, Vinicius Cristian O.; Martins, Carlos H. G. (Springer Nature, 2018)
In this work, a series of lactone 1,4-dihydroquinoline derivatives 4 were efficiently synthesized and characterized by 1H and 13C NMR. The synthesized compounds were evaluated for their in vitro antibacterial activity against the bacterial strains Porphyromonas gingivalis, Prevotella nigrescens, Streptococcus mitis, and Streptococcus sanguinis and against Mycobacterium tuberculosis, Mycobacterium avium and Mycobacterium kansasii. The results revealed that the evaluated compounds were more active against Gram negative bacteria. Compounds 4ba, 4bb, 4bg, 4bi, 4bn, 4ch, and 4ci displayed moderate antibacterial activity against P. gingivalis. 4bi was the most active compound against the three strains of Mycobacterium. Based on structure–activity relationship studies, we observed that the presence of a nitro group on the benzylic ring and a methylenedioxy group on the dihydroquinoline ring enhanced the antibacterial activity of the derivatives.
Keywords: antibacterial activity; Azo-heterocyclic compounds; quinoline derivatives